PELAKSANAAN KEBIJAKAN PENYERTAAN MODAL TERHADAP KINERJA PERUSAHAAN DAERAH AIR MINUM TIRTA INDRAGIRI TAHUN 2015 - 2016 - Febriandi, Yoga Ramadhan; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was motivated by the poor performance of the Regional Water Supply Company of Tirta Indragiri Hilir from year to year. There are problems that always convolute Regional Companies from year to year, such as the low amount of water production, poor water distribution, old pipes, and poor water quality. How is the influence of investment policy of Local Government Equity Participation on Regional Water Supply Company of Tirta Indragiri Hilir. This study aims to determine the Implementation of Equity Policy on the Performance of Tirta Indragiri Regional Drinking Water Companies in 2015-2016. The type used in this study is a type of descriptive research with a qualitative research approach. The type of research data is primary data and secondary data. Data collection techniques in this study are documentation and interviews. Data analysis techniques used were qualitative descriptive data analysis.Based on the results of the study indicate that the capital investment provided by the Regional Government of Indragiri Hilir Regency has not achieved the desired objectives, this is due to the existence of a complaint report shown to the Regional Water Supply Company Tirta Indragiri Hilir in the provision of clean water and the Regional Company Ar Minum Tirta Indragiri Hilir must be more observant in improving the quality that is channeled to customers and not forgetting to coordinate with all parties involved in the progress of the Tirta Indragiri Regional Water Supply Company in pipe rejuvenation and improvement of technical capacity by establishing good relations supported by quality human resources from both partiesKeywords: Policy, equity participation